Exploring pollen resources of himalayan bumblebees: A scanning electron microscopy analysis of Angiosperm interactions (Bangladesh Journal of Botany, 2026)
This study investigates the role of the bumblebees in sustaining plant-pollinator networks, genetic diversity and ecosystem resilience in the Indian Himalayan Region (IHR). Sixteen species were documented across eight angiosperm families with Asteraceae as the dominant floral resource. Foraging patterns revealed both specialized and generalist strategies while pollen morphology and species specific distributions highlighted the adaptability of some taxa and the vulnerability of high altitude specialists. Using Scanning Electron Microscopy (SEM), pollen grains attached to different body parts especially the hind legs were identified and linked to plant families revealing intricate pollination networks. These findings demonstrate bumblebees’ capacity to pollinate multiple plant species, facilitating cross-pollination and enhancing ecosystem stability. Conservation efforts should focus on protecting diverse floral resources particularly Asteraceae and Balsaminaceae, while long-term monitoring and advanced analytical approaches are essential to assess climate change impacts and support effective pollinator conservation in the mountain ecosystems.Bangladesh J. Bot. 55(1): 85-91, 2026 (March)